Piracy at the Frontier: Uneven Development and the Public Sphere. Issue 1 (August 2014) - Athique, Adrian
In the decades following Indian Independence, the exponential growth of urban populations, the encroachment of slums on all open lands, the expensive and exhaustive hurdles to commercial premises and the chronic shortage of leisure capacity in overcrowded Indian cities all contributed to a delivery mechanism that operated on the street. Even during the heady days of India's 'liberalisation' economy at the end of the millennium, India's media revolution – notwithstanding its global interface with content and technology – was essentially a street economy. Its commercial aesthetics were embedded within the particular spaces of video parlors, pavement stalls and the unique self-regulating confines of India's residential colonies. As such, the public encounter with media technologies was marked by appropriation, informality and opportunistic mobility, and it was firmly embedded in local relationships of exchange. Over the past decade, however, an emerging corporate leisure economy has sought to implement a very different social architecture. Its commercial strategy is overwhelmingly determined by the notion of an 'aspirational' middle class, 'unfettered' by liberalisation. Its public domain has been materialised in the new infrastructure of shopping malls and multiplexes designed to physically distance consumers from the 'Third World' media economy of the recent past. At the same time, the explicit alignment of this emerging corporate leisure economy with the 'consuming classes' undermines its substitution for more inclusive localised domains served by the pirate public sphere. This article argues that attempts to relocate media consumption within the formal economy and the strictures of 'international' architecture necessarily illustrate the ongoing tensions between two distinctive and incompatible public spheres.